Enhancement of properties of PA6/PP nanocomposites via organic modification and compatibilization (eXPRESS Polymer Letters)
Nanocomposites based on polyamide 6/polypropylene (PA6/PP = 70/30) blend containing organophilic montmorillonite (OMMT) and maleated polypropylene (PP-g-MA) as compatibilizer were prepared by melt compounding followed by injection molding. Modification of montmorillonite (MMT) with dodecyalmine was successfully performed. The morphological and mechanical properties of nanocomposites were investigated by using x-ray diffraction (XRD), transmission electron microscopy (TEM), tensile, flexural, and impact tests. The thermal stability of nanocomposites was characterized by using thermogravimetric analysis (TGA) and heat distortion temperature (HDT). XRD and TEM results indicated that the intercalated structure was obtained for PA6/PP/MMT composite, a mixture of intercalated and exfoliated structures for PA6/PP/OMMT nanocomposite, and exfoliated structure for PP-g-MA compatibilized PA6/PP/OMMT nancomposite. Thermal stability and HDT of PA6/PP matrix were improved by the addition of both MMT and OMMT. The introduction of PP-g-MA into the PA6/PP/OMMT nanocomposite enhanced the properties such as stiffness, strength, ductility, impact strength, and HDT. This was attributed to the compatibilizing effect of PP-g-MA which improved interfacial adhesion between OMMT with PA6/PP matrix and also promoted the degree of exfoliation of silicate layers in the PA6/PP matrix.